2017
DOI: 10.1016/j.jcm.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic Treatments for Idiopathic Scoliosis: A Narrative Review Based on SOSORT Outcome Criteria

Abstract: Objective: The purpose of this review was to evaluate the current body of literature on chiropractic treatment of idiopathic scoliosis against the 2014 consensus paper of the Society on Scoliosis Orthopedic and Rehabilitation Treatment (SOSORT) and the Scoliosis Research Society (SRS) Non-Operative Management Committee for outcome reporting in nonoperative treatments. Methods: A search of the PubMed and Index to Chiropractic Literature databases for studies published from January 2000 through February 2016 det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The initial Risser stage is important for the research on patients with immature IS. For example, a stable Cobb angle from Risser 0 to Risser 3 may have better therapeutic benefits than a 6°curve correction during Risser 4 ( 13 ). Furthermore, the included studies did not report the number of patients with Cobb change of 6°or more, which was an improved standard in Cobb angles by the SOSORT and SRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial Risser stage is important for the research on patients with immature IS. For example, a stable Cobb angle from Risser 0 to Risser 3 may have better therapeutic benefits than a 6°curve correction during Risser 4 ( 13 ). Furthermore, the included studies did not report the number of patients with Cobb change of 6°or more, which was an improved standard in Cobb angles by the SOSORT and SRS.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that mean changes in the Cobb angles are less than 6°before and after the intervention ( 22 , 28 , 32 ). In addition, a minimum of 5-year follow-up period for adults with IS was recommended by the SOSORT criteria ( 13 ). There is little evidence of long-term effects of manual therapy on the Cobb angles.…”
Section: Discussionmentioning
confidence: 99%
“…The previous reviews did not draw reliable conclusion on the effects of manual therapy in the management of IS because it cannot be reliably evaluated the relevant effects due to no enough eligible studies to conduct data synthesis in the meta-analysis. [ 16 19 ] In the last decade, however, several new RCTs were published. Therefore, the meta-analysis on the effects of manual therapy for IS could be performed to fill this evidence gap in our review.…”
Section: Discussionmentioning
confidence: 99%
“…The previous reviews did not draw reliable conclusion on the effects of manual therapy in the management of IS. [ 16 19 ] The effects of manual therapy in the management of IS cannot be reliably evaluated because there were no enough eligible studies to conduct data synthesis in the meta-analysis. Most relevant studies were observational case studies or small-scale clinical trials with poor methodology.…”
Section: Introductionmentioning
confidence: 99%